Pengaruh Motivasi Kerja dan Kepuasan Kerja terhadap Kinerja Karyawan yang Dimoderasi Lama Kerja (Studi pada Karyawan Galaxy Solusindo di Kota Malang) - Survival, Survival; Wulandari, Wahju; Quthni, Muhammad Darul; Fa’riyah, Nisaul; Sa’diyah, Nahdya Halimatus (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This study aims to understand how work motivation and job satisfaction influence employee performance, while also considering the role of tenure as a moderating factor. The research was conducted at Galaxy Solusindo in Malang City, involving all employees of the company. Using a total sampling method, 85 employees participated by completing a questionnaire, and the collected data was analyzed using Smart Partial Least Square (PLS) software. The findings indicate that work motivation, job satisfaction, and tenure all have a significant and positive impact on employee performance. Furthermore, tenure has been found to either strengthen or weaken the effect of motivation and job satisfaction on performance. In other words, employees with longer tenure tend to demonstrate better performance, driven by higher levels of motivation and job satisfaction.